Brugen af Mosesfortællingerne hos Paulus og Josefus - Damgaard, Finn (Dansk Teologisk Tidsskrift, 2008)
The article demonstrates how the ancient concept of o9mo/noia (concord) was crucial for Paul’s and Josephus’ use of the Moses narratives. In continuation of Margaret M. Mitchell’s dissertation Paul and the Rhetoric of Reconciliation, I argue that Paul in 1 Cor 10:1-11 uses the Moses narratives to exhort the Corinthians to become re-unified. Paul’s use of these narratives and his use of himself as an example to imitate in his struggle for o9mo/noia are compared to the way Josephus rewrites Moses in his Jewish Antiquities as a founding figure that both establishes and re-establishes a Jewish o9mo/noia. In so doing, Josephus presents Moses in a way very similar to how he has depicted himself in the Jewish War and similarly to the way he later portrays himself in his Vita. Josephus demonstrates thus in his own portrait that the story of Moses has to be re-narrated and even repeated if the Jewish community shall continue to exist.